Fossilization model for squamastrobus tigrensis foliage in a volcanic-Ash deposit: Implications for preservation and taphonomy (podocarpaceae, lower cretaceous, Argentina) - Lafuente Diaz, Maiten Amalia (2018)
The present study is a holistic approach to the relationship between volcaniclastic host rock characteristics and the fossilization processes of short leafy coniferous branches of Squamastrobus tigrensis, preserved as fossilized-cuticles (Lower Cretaceous, Baqueró Group, Patagonia, Argentina). The question of diagenetic influences of Aptian volcaniclastic sedimentation on preservation chemistry and taphonomic processes is addressed. Whereas infrared spectroscopy provided chemical information on the leaves, vitrinite reflectance and complementary thermal indicators provided data on the thermal maturity of the dispersed organic matter in the host rock. Three sample types were analyzed: Fossilized-cuticle, macerated fossilized-cuticle (by infrared spectroscopy), and associated organic host rock matter (by light microscopy). Results clearly show chemical variability between, and within the fossilized-cuticle and cuticle, as well as a similarity to type I/II kerogen, i.e., high contents of both aliphatic groups and oxygencontaining compounds. Combined with the lower maturity of the host rock, the importance of the depositional environment during burial and taphonomic conditions that affected the fossilization of S. tigrensis are summarized in a general fossilization model.